MACAM-MACAM SPLIN PADA PERAWATAN GANGGUAN SENDI TEMPOROMANDIBULA - Ira Tanti; Laura Susanti Himawan (Faculty of Dentistry, Universitas Indonesia, 2015)
Splint or orthopedic appliances is routinely used in the treatment of temporomandibular disorders (TMD). This appliance is used to alter occlusal relationship and to redistribute occlusal forces, to prevent wear and mobility of the teeth, to reduce bruxism and parafunction, to treat masticatory muscle pain and dysfunction, and to alter structural relationship of the TMJ. There are 2 kinds of splint, the permissive and non permissive. Stabilization splint and bite plane are permissive splints, and anterior repositioning appliance is a non permissive splint. Each kind of splint has its own indication. There is strong evidence that splint therapy is successful in the treatment of TMD, but there is no consenses of opinion on how splints work.